Comparison of two different skin preparation strategies for open cardiac surgery - Muhammet Onur Hanedan; Ertekin Utku Unal; Aysen Aksoyek; Veysel Basar; Sercan Tak; Ufuk Tutun; Hasan Isik; C.Levent Birincioglu (Journal of Infection in Developing Countries)
Introduction: Surgical site infection (SSI) is a serious complication after cardiac surgery; skin preparation is an important step in the prevention of wound contamination with skin flora. In this study, two different skin preparation strategies (standard povidine iodine cleaning plus plain adhesive drape and microbial sealant (InteguSeal, Kimberly-Clark Health Care, Roswell, GA, USA) were compared in cardiac surgery patients. Methodology: This prospective study included 96 cardiac surgery patients randomized to either a standard plain adhesive drape (28 patients, control group) or a microbial sealant (68 patients, study group). Bacterial isolates were obtained from the wounds in the operating room before the skin incision and after the surgical procedure had ended. Results: Microorganisms were isolated from 38 patients (39.6%) in the study population. Twenty-seven of these patients were from the microbial sealant group and 11 were from the plain adhesive drape group. No postoperative wound infection was encountered in either group. No statistically significant differences between the two groups regarding the number of patients with microorganism isolation (p = 0.974) or postoperative leukocyte counts and neutrophil granulocyte percentages were observed. Conclusions: Regarding SSI after cardiac surgery, microbial sealant is equivalent to the standard skin preparation strategy applied with povidine iodine cleaning and a plain adhesive drape.